O retrato brasileiro da qualidade da representação política dos conselhos gestores municipais de assistência social (2010-2016) - Moreira, Liége Torresan (2018)
Considering the current debate regarding the new representation modalities initiated by Participative Institutions (PI), this work makes an evaluation of political representation quality in the Town Councils of Social Assistance from 2010 to 2016. The variables used for this evaluation embrace three analytical dimensions: 1- Choosing processes of representatives and parity, 2 ? Capacity of making the decisions public and 3 ? Counselors profiles. In order to generate a picture of the political representation aspects within this PI, it was used the Censo SUAS (2010 to 2016) database, which was applied by MDS in more than 90% of the Brazilian cities, e along with it, the National Social Assistance Policies (NSAP) guidelines. Our main discoveries are the consolidation of more bureaucratic elements related to the representation of these councils, the difficulty in simplifying the interaction spaces among represented and representatives and the distinctions regarding the counselor profile in the biggest Brazilian regions